Cosmic Education in Maria Montessori: Arts and Sciences as resources for human development - Rossella Raimondo (Firenze University Press, 2019)
This article reflects on the concept of cosmic education set out by Maria Montessori in strict correlation to those of cosmic vision and cosmic plan. Cosmic education is considered here as a fundamental direction within the original core of the thought of Maria Montessori since the early twentieth century. Among the different orders of consideration that support the actuality of cosmic education, two are the object of analysis. The first concerns the content plan that aims to create interactions with the various disciplinary fields (scientific, historical and geographical education, etc.) as a unitary vision and development of knowledge. The second concerns the existential level: it embraces and summarizes the concepts of "ecological education", "education for peace", and "education for the world" in themselves to the point of recalling implications of ethical and aesthetic education.